2006
DOI: 10.1016/j.crte.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Imaging spectroscopy of changing Earth's surface: a major step toward the quantitative monitoring of land degradation and desertification

Abstract: Imaging spectroscopy makes direct identification of surface materials possible in a spatial context based on diagnostic visible and near-infrared properties. Advanced methodologies permit the deconvolution of complex surface signatures. It opens a number of possibilities for characterizing and monitoring mineralogical and/or biogeochemical surface properties and changes, particularly in the field of land desertification, where understanding of processes involve the quantitative description of the interplay bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The importance of high spectral resolution has been acknowledged in several studies (e.g., Hill et al 1999;Pinet et al 2006;Escribano et al 2010), particularly because additional diagnostic bands in the short-wave infrared region (due to the presence of cellulose, lignin, and other organic components) may support discrimination between biocrusts and soils. Also Ustin et al (2009) confirmed the important potential of hyperspectral imagery, since they could identify experimental treatments of biological soil crusts as part of a long-term manipulative experiment.…”
Section: Spectral Indicesmentioning
confidence: 98%
“…The importance of high spectral resolution has been acknowledged in several studies (e.g., Hill et al 1999;Pinet et al 2006;Escribano et al 2010), particularly because additional diagnostic bands in the short-wave infrared region (due to the presence of cellulose, lignin, and other organic components) may support discrimination between biocrusts and soils. Also Ustin et al (2009) confirmed the important potential of hyperspectral imagery, since they could identify experimental treatments of biological soil crusts as part of a long-term manipulative experiment.…”
Section: Spectral Indicesmentioning
confidence: 98%
“…Based on these indices retrieved from images, various assessment models such as decision tree classification, unsupervised classification and micrometeorological conditions of land surface like temperature, wind and albedo have been used to characterize desertification. These changes of land surface conditions make the spectral characteristics of desertification land vary greatly to different degrees, which could be captured by satellite sensors and this might be fundamental for the analysis of desertification by means of the indices derived from satellite images (Pinet et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Land surface albedo is an important indicator that determines energy budget and the change of micrometeorological conditions like temperature, aridity/humidity etc. of land affected by desertification (Pinet et al, 2006). For the present surface albedo the MODIS product (called MOD43C1) of white-sky (completely diffuse) and blacksky (direct beam) is adopted (Gao et al, 2005;Lucht et al, 2000;Schaaf et al, 2002) (available at http://modarch.gsfc.nasa.gov/ MODIS/LAND/#albedo-BRDF), (Lucht et al 2000), (Schaaf et al 2002), and MOD43 User's Guide, available at http://geography.bu.edu/brdf/userguide/.…”
Section: Methodsmentioning
confidence: 99%
“…These narrow spectral wavelengths allow the identification of characteristic spectral attributes for the mapping and monitoring of vegetation at species levels in different ecosystems (Thenkabail et al, 2004;Zwiggelaar, 1998). In spite of the great capability of remote sensing to provide detailed spectral information, the mapping of vegetation species using hyperspectral remote sensing data is challenging due to data dimensionality, data processing, and the fact that the images are too prohibitively expensive to use (Metternicht et al, 2010;Okin et al, 2001;Pinet et al, 2006;Schmidtlein and Sassin, 2004;Underwood et al, 2003). However, multispectral data is relatively available, at a low cost, and does not require complex preprocessing and processing techniques.…”
Section: Introductionmentioning
confidence: 99%